Change in Antimicrobial Therapy Based on Bronchoalveolar Lavage Data Improves Outcomes in ICU Patients with Suspected Pneumonia - Bharti Chogtu; Vrinda Mariya Elenjickal; Dharma U. Shetty; Mahsheeba Asbin; Vasudeva Guddattu; Rahul Magazine (Critical Care Research and Practice)
Flexible bronchoscopy (FB) is often performed in critically ill patients with suspected pneumonia. It is assumed that there will be an association with improved outcomes when bronchoalveolar lavage (BAL) data lead to a change in antimicrobial therapy. Methods. This study included a retrospective cohort of intensive care unit (ICU) patients who underwent FB for a diagnosis of suspected pneumonia. The study compared the outcome of patients in whom antimicrobial modification was carried out based on BAL reports versus those in whom it was not carried out. Cases where the procedure could not be completed or had incomplete records were excluded. The FB reports were accessed from the register maintained in the Department of Respiratory Medicine. The demographic details, clinical symptoms, laboratory investigations, and microbiological and radiology reports were recorded. Data on the antmicrobial therapy that the patients received during treatment and the outcome of the treatment were obtained from the case records and noted in the data collection form. Results. Data from a total of 150 patients admitted to the ICU, who underwent FB, were analyzed. The outcomes in the group where antimicrobial modification based on bronchoalveolar lavage (BAL) fluid reports was carried out versus the no-change group were as follows: expired 23, improved 82, unchanged 8 versus expired 12, improved 18, and unchanged 7 (p=0.018); total duration of ICU stay 13.12 ± 10.61 versus 19.43 ± 13.4 days (p=0.012); and duration from FB to discharge from ICU 6.33 ± 3.76 days versus 8.46 ± 5.99 (p=0.047). The median total duration of ICU stay and clinical outcomes were significantly better in the nonintubated patients in whom BAL-directed antimicrobial modification was implemented. Distribution of microorganisms based on BAL reports was as follows: Acinetobacter baumanii 45 (30%), Klebsiella pneumoniae 37 (24.66%), Escherichia coli 9 (6%), and Pseudomonas aeruginosa 9 (6%). Conclusion. A change in antimicrobial therapy based on BAL data was associated with improved outcomes. The commonest bacterial isolate in the BAL fluid was Acinetobacter baumanii.